Photoresponsive DNA-cross-linked hydrogels for controllable release and cancer therapy - Kang, Huaizhi (Langmuir : the ACS journal of surfaces and colloids, 2011)
We have developed a photoresponsive DNA-cross-linked hydrogel that can be photoregulated by two wavelengths with a reversible sol-gel conversion. This photoinduced conversion can be further utilized for precisely controllable encapsulation and release of multiple loads. Specifically, photosensitive azobenzene moieties are incorporated into DNA strands as cross-linkers, such that their hybridization to complementary DNAs (cDNAs) responds differently to different wavelengths of light. On the basis of the rheology variation of hydrogels, it is possible to utilize this material for storing and releasing molecules and nanoparticles. To prove the concept, three different materials--fluorescein, horseradish peroxidase, and gold nanoparticles--were encapsulated inside the gel at 450 nm and then released by photons at 350 nm. Further experiments were carried out to deliver the chemotherapy drug doxorubicin in a similar manner in vitro. Our results show a net release rate of 65% within 10 min, and the released drug maintained its therapeutic effect. This hydrogel system provides a promising platform for drug delivery in targeted therapy and in biotechnological applications